2021
DOI: 10.3390/cancers13040889
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-Catenin Signaling and Immunotherapy Resistance: Lessons for the Treatment of Urothelial Carcinoma

Abstract: Urothelial cell carcinoma (UCC) is a significant public health burden. It accounts for approximately 90 percent of all bladder cancers with an estimated 200,000 annual deaths globally. Platinum based cytotoxic chemotherapy combinations are the current standard of care in the frontline setting for metastatic UCC. Even with these treatments the median overall survival is estimated to be about 15 months. Recently, immune checkpoint inhibitors (ICIs) have demonstrated superior clinical benefits compared to second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 74 publications
(154 reference statements)
1
24
0
Order By: Relevance
“…Therefore, it is plausible to hypothesize that some patients harbor genetic events that confer resistance to ICIs. In this regard, aberrant activation of Wnt/β-catenin has emerged as an important pathway mediating ICI resistance (138,139). Harding et al reported that in HCC patients treated with ICIs, activation of the Wnt/β-catenin pathway correlates with lower disease control rate and lower progression-free and overall survival rates (140).…”
Section: Targeting Wnt/β-catenin For Hcc Treatmentmentioning
confidence: 99%
“…Therefore, it is plausible to hypothesize that some patients harbor genetic events that confer resistance to ICIs. In this regard, aberrant activation of Wnt/β-catenin has emerged as an important pathway mediating ICI resistance (138,139). Harding et al reported that in HCC patients treated with ICIs, activation of the Wnt/β-catenin pathway correlates with lower disease control rate and lower progression-free and overall survival rates (140).…”
Section: Targeting Wnt/β-catenin For Hcc Treatmentmentioning
confidence: 99%
“…Furthermore, a study of polymorphisms in 40 genes of the Wnt/β-catenin signaling pathway has suggested that variants may play a role in the etiology of bladder cancer [ 9 ]. With regard to therapy resistance, it has recently been documented that the Wnt/β-catenin pathway may be involved in resistance to cisplatin [ 10 ], doxorubicin [ 11 , 12 ], and immunotherapy [ 13 ] in bladder cancer. To our knowledge, its role in the acquisition of paclitaxel or docetaxel resistance has not been described.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, these observations suggest that SFRP2, a putative Wnt inhibitor, may function at the interactions between tumor cells and fibroblasts in UC development. Nevertheless, the Wnt/β-catenin signaling has also been suggested to drive cytotoxic T cell exclusion by modulating the crosstalk between tumor cells and tumor-associated macrophages (TAMs) and lead to immunotherapy resistance in UC treatment ( 12 ). These further highlight the complexity of the TME that creates a favorable niche to reduce treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…However, accumulated investigations have shown incompatible evidence between the Wnt/β-catenin signaling and UC carcinogenesis ( 10 , 11 ). Additionally, the aberrant Wnt/β-catenin signaling is not only restricted to cancer cells but also implicated in dynamic interactions with the tumor microenvironment (TME) and immune system in UC ( 12 ). These observations further emphasize the molecular heterogeneity of UC, and a deeper understanding of the molecular characterization of UC may come up with more hints for how such pathways be therapeutically targeted.…”
Section: Introductionmentioning
confidence: 99%